The contemporary in heritage: experimental models of revitalization using the case study of Villa Moser by architect Milan Zloković - Ciganović, Aleksa (Arhitektura i urbanizam, 2023)
Belgrade City Institute for the Protection of Cultural Monuments, October 20 - November 20, 2023. Exhibition of final projects from the 2022/23 generation of Master’s academic studies in Interior Architecture at the University of Belgrade - Faculty of Architecture
Keywords: Belgrade City Institute for the Protection of Cultural Monuments; Exhibition of final projects; Master academic studies